In‐depth prospection of Avène Thermal Spring Water reveals an uncommon and stable microbial community. (1st September 2020) - Bourrain, M.; Suzuki, M.T.; Calvez, A.; West, N.J.; Lions, J.; Lebaron, P.
Abstract: Background: Avène Thermal Spring Water (TSW) exhibits therapeutic properties in the treatment of skin pathologies. Arising from a dolomitic aquifer system, its physico‐chemical properties are well‐established and its bacteriological quality regularly monitored. The microbiota of this aquifer have been characterized. Objectives: We aimed to describe the structure of the bacterial community inhabiting the deep aquifer and to examine its dynamics over time. Methods: The Avène TSW was collected at the catchment point and filtered through 0.1 µm pore size filters. The sampling was carried out every 3 months to generate a 4‐year time series. The DNA extracted from filters was analysed using high‐throughput 16S rRNA gene amplicon sequencing, and the microorganisms and their contribution were characterized by the taxonomic assignment of sequence variants generated from each sample. Results: Bacteria were distributed into 39 phyla. Nitrospirae and Proteobacteria were the most prevalent, accounting for 38% and 23% of the total community on average, respectively. A stable pattern was observed throughout the study. A few bacterial species were always detected, forming a core community of likely chemolithoautotrophic organisms which might use energy sources and nutrients produced from water–bedrock interactions. Most of the species were distantly related to organisms described to date. Conclusions: Avène TSW provided by the deep aquifer system harbours a unique microbial community, shaped by the physico‐chemical characteristics of the deep environment. Its remarkable stability over time has revealed a high level of confinement of the water resource.